Genome-Wide Identification of lncRNAs Involved in Fertility Transition in the Photo-Thermosensitive Genic Male Sterile Rice Line Wuxiang S - Wang, Ying; Zhang, Hongyuan; Li, Qian; Jin, Jing; Chen, Hao; Zou, Yu; Huang, Xingguo; Ding, Yi (Frontiers in Plant Science, 2021)
Long non-coding RNAs (lncRNAs) act as universal regulators of various biological processes, but no genome-wide screening of lncRNAs involved in the fertility transition of the photo-thermosensitive genic male sterile (PTGMS) rice line has been reported. Here, we performed strand-specific RNA sequencing (ssRNA-seq) at three developmental stages of a novel PTGMS line Wuxiang S (WXS). A total of 3,948 lncRNAs were identified; 622 of these were detected as differentially expressed lncRNAs (DE-lncRNAs) between male-sterile WXS (WXS-S) and male-fertile WXS (WXS-F). A large proportion of lncRNAs differentially expressed at the stage of pollen mother cells (PMCs) meiosis, suggested that it may be the most critical stage for fertility transition of WXS. And, functional annotation of the cis- and trans- targets of DE-lncRNAs showed that 150 targets corresponding to 141 DE-lncRNAs were identified as involved in anther and pollen development. Moreover, computational analysis predicted 97 lncRNAs as precursors for 72 miRNAs, and 94 DE-lncRNAs as potential endogenous target mimics (eTMs) for 150 miRNAs. Finally, using the dual luciferase reporter assays, we demonstrated that two lncRNAs act as eTMs to regulate the expression of the SPL and GRF genes by competing for the shared osa-miR156 and osa-miR396, respectively. These genomic characteristics, differential expression, and interaction of lncRNAs with miRNAs and mRNAs contribute to our understanding of the roles of lncRNAs during the fertility transition in PTGMS rice lines.